Guinea : Poverty Reduction Strategy Paper; Third Annual Progress Report. (IMF Staff Country Reports; Country Report ;, 2007)
This paper discusses key findings of the Third Annual Progress Report (APR) on the Poverty Reduction Strategy Paper (PRSP) for Guinea. The PRS implemented by the government since 2002 has the overall objective of reducing poverty significantly and sustainably, by increasing incomes and improving the well-being of the population, and particularly of its poorest segments. The APR reveals that in social sectors, and particularly in health, village hydraulics, and education, indicators have improved despite financial constraints. The gross enrollment rate rose from 77 percent to 79 percent at the national level.